Android Robot-Mediated Mock Job Interview Sessions for Young Adults with Autism Spectrum Disorder: A Pilot Study - Kumazaki, Hirokazu; Warren, Zachary; Corbett, Blythe A.; Yoshikawa, Yuichiro; Matsumoto, Yoshio; Higashida, Haruhiro; Yuhi, Teruko; Ikeda, Takashi; Ishiguro, Hiroshi; Kikuchi, Mitsuru (Frontiers in Psychiatry, 2017)
The feasibility and preliminary efficacy of an android robot-mediated mock job interview training in terms of both bolstering self-confidence and reducing biological levels of stress in comparison to a psycho-educational approach human interview was assessed in a randomized study. Young adults (ages 18 – 25) with autism spectrum disorder (ASD) were randomized to participate either in a mock job interview training with our android robot system (n=7) or a self-paced review of materials about job-interviewing skills (n=8). Baseline and outcome measurements of self-reported performance/efficacy and salivary cortisol were obtained after a mock job interview with a human interviewer. After training sessions, individuals with ASD participating in the android robot-mediated sessions reported marginally improved self-confidence and demonstrated significantly lower levels of salivary cortisol as compared to the control condition. These results provide preliminary support for the feasibility and efficacy of android robot-mediated learning.